Práticas e perspectivas para o ensino de microbiologia no contexto amazônico - Souza, Afonso Santos de (2020)
Learning can be built based on our experiences and through interactions with the community. In this sense, it is important to teach new knowledge at school based on regional context, so that it can get closer to the reality of the individuals in the learning process. In the case of microbiology, which is part of the curricular content of Biology in High School, this premise is even more relevant, given the complexity of the content and the invisibility of microorganisms. Therefore, the objective of this dissertation was to elaborate on a microbiology teaching strategy based on the Amazonian microbiota, proposing a didactic sequence based on the assumptions of David Ausubel's meaningful learning. The development of this research took place in two distinct stages: the first consisted of the analysis of high school textbooks, to verify how the microbiology contents were contemplated in these works, and in some way, microorganisms from the Amazon were mentioned. In parallel, a survey was carried out about published works that are easily accessible on the web, which used some Amazonian microorganisms as the object of study, from the perspective that they could subsidy to teach microbiology topics. The second stage of the research was subdivided into 6 meetings with 30 students from two classes of the 3rd year of high school at a state full-time school in Manaus, in the State of Amazonas. In this stage, previous organizers and concept maps were used as instruments for data collection, diagnosis, and evaluation. The maps were applied individually and collaboratively and analysed using Topological Taxonomy and Analytical Rubrics, containing criteria that describe the qualities that should be highlighted during the evaluation, namely, the levels of performance, and the quality of performance, which it is the description of what the teacher expects each student to achieve. The results obtained showed that the textbooks did not include regional content, demonstrating the lack of support materials for contextualization at the regional level. We verified through a systematic survey, that there are countless published scientific works on microorganisms in the Amazon and that they could be used for direct application in the classroom. The application of the didactic sequence showed the enhancement of learning in microbiology exemplified with Amazonian content, causing a noticeable increase in students' empathy for the topics covered, and is reflected in the evaluation of the final conceptual maps. Therefore, the didactic sequence proposed here proved to be valid to facilitate the acquisition of knowledge of microbiology contextualized in the Amazon. And yet, both the evaluative and analytical instruments proved to be adequate and useful for teaching general microbiology and in the Amazon context.